The Impending Effect of Tuberculosis on Human Health: Major Concerns and Challenges - Mishra, J. K. (National Geographical Journal of India, 2022)
This article is an attempt to elucidate how tuberculosis (TB) as a disease impacts human health and is a greatest public health challenge in the world, especially in the developing parts. It discusses global and national TB scenario, its transmission, probable infection situations, general symptoms, diagnosis and treatment, control practices, and degree of its fatality in coinfection with the HIV.